Про зміст поняття «персонал органів та установ виконання покарання» та його системоутворюючі ознаки - Яковець, І.; Новосад, Ю.; Iakovets, I.; Novosad, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2017)
В статті, на підставі вивчення наукових і нормативно-правових джерел, сформульовано авторське визначення поняття «персонал органів та установ виконання покарань» та виведені системоутворюючі ознаки, що складають його зміст, а також здійснено їх аналіз у контексті досліджуваного об’єкта. The article considers the author's definition of the concept of «personnel of the bodies and institutions for the execution of sentences». The definition and the system-forming features of the concept that make up its content are argued on the basis of the study of scientific and regulatory sources. The article provides their analysis in the context of the investigated object. The author believes that full, essentially meaningful content of the concept of «personnel of the bodies and institutions for the execution of sentences» can be outlined only on the basis of the full analysis of any and all of its features. On the other hand, the absence of at least one of the aspects not only distorts the socio-legal nature of the subject of the criminal-executive legal relations, but also creates certain obstacles for improving its legal status and sphere of execution of sentences on the whole. The theoretical significance of the formulated in this paper concept is that for the first time the concept «personnel of bodies and institutions for execution of sentences» is deduced on the scientific level, while in the doctrinal sources it has been considered only in the context of the penitentiary institutions activity, leaving without any scientific explanation the meaning of the other – «personnel of the penal institutions for the execution of sentences», although the relationship of it with the former is obvious and objectively predetermined.
On the Concept of «Personnel of the Penitentiary Institutions for the Execution of Sentences» and Its System-Creating Characteristics
Keywords: кримінально-виконавче законодавство; сфера виконання покарань; персонал органів та установ виконання покарань; виконання покарань; відбування покарань; завдання; кваліфікаційні вимоги; принципи права; criminal-executive legislation; penal sphere; personnel of penitentiary bodies and institutions for the execution of sentences; execution of sentence; serving punishment; task; qualification requirements; the principles of law